Oxidation for unsymmetrical bromo-1, 10-phenanthrolines and subsequent hydroxylation, decarbonylation and chlorination reactions. Issue 34 (23rd August 2018) - Peng, Yu-Xin; Hu, Bin; Huang, Wei
Abstract: A systematic investigation on the oxidation of unsymmetric bromo-phens is presented herein, where the reaction temperature is found to be the key parameter to generate oxidation or oxidation-bromination products. The regioselective C3-brominated compounds are produced in moderate yields in the cases of 2-bromo-phen and 4-bromo-phen. Subsequent hydroxylation and decarbonylation for bromo-phds are also studied, where a series of bromo-diazafluorenones and phen-triones have been isolated. Furthermore, various chlorination products have been obtained by treating bromo-phds or bromo-phts with excess POCl3 . Graphical abstract: